ASSESSMENT OF YIELD COMPONENT TRAITS IN CORIANDER OVER ENVIRONMENTS - SANGEETA YADAV,; ARUN KUMAR BARHOLIA, (The Bioscan, 2015)
Thirty five genotypes including the land races of Madhya Pradesh were tested in four environments to assess the yield component characters in coriander over environments using correlation and path coefficient analyses. The environments created by adjusting fertility status of the soil in two subsequent years of 2008-09 and 2009 -10. Seed yield per plant was positively and significantly correlated with branches per plant (0.219), plant height (0.602) and umbellate per umbel (0.556) but it was negatively and significantly associated with days to 50% flowering (-0.452) and maturity days (-0.452) over the environments. Plant height (0.639, 0.630, 0.620 and 0.528) and umbellate per plant (0.657, 0.693, 0.579 and 0.528) exhibited significant and positive correlation with seed yield per plant in all the environments. The direct contribution of maturity days (0.208), branches per plant (0.026), plant height (0.300) and umbels per plant (0.089) on seed yield per plant was positive over the environments. These traits thus appeared as major and stable yield component traits. It may be thus concluded that direct selection based on phenotypic performance of these traits would be advantageous for genetic improvement in seed yield of coriander.